IMPLEMENTASI METODE TILAWATI DALAM PENGEMBANGAN KEMAMPUAN TADARUS SISWA KELAS V MI PEMBANGUNAN UIN JAKARTA - Muhamad Muhyidin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Qur'anic learning at the elementary madrasah level requires a structured and engaging method that accommodates differences in students' reading abilities. This study aims to describe the implementation of the Tilawati method, analyze the teacher's role, and examine the development of Qur'anic recitation skills among fifth-grade students at MI Pembangunan UIN Jakarta. A descriptive qualitative approach was employed. Data were collected through classroom observations, interviews with the principal, one Tilawati teacher, 22 students of class V B, and two parents, as well as documentation of the learning program. Data analysis involved data condensation, data display, and conclusion drawing, while trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings show that the Tilawati method was implemented through classical instruction, individual read-and-listen practice, immediate correction, periodic evaluation, and habituation through the Khotmul Qur'an program. These procedures supported improvements in reading fluency, tajwid accuracy, rhythmic consistency, and students' confidence in recitation. The teacher acted as a reading model, guide, motivator, and evaluator. Supporting factors included teacher competence, a religious school culture, structured institutional programs, and family support. The main constraints were differences in students' initial abilities, limited instructional time, and uneven parental assistance at home. The study concludes that the Tilawati method is effective when consistently implemented and reinforced by collaboration between the school and families. ABSTRAK Pembelajaran Al-Qur'an pada jenjang madrasah ibtidaiyah memerlukan metode yang terstruktur, menarik, dan mampu mengakomodasi perbedaan kemampuan siswa. Penelitian ini bertujuan mendeskripsikan implementasi metode Tilawati, menganalisis peran guru, serta mengkaji perkembangan kemampuan tadarus Al-Qur'an siswa kelas V MI Pembangunan UIN Jakarta. Penelitian menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui observasi pembelajaran, wawancara dengan kepala madrasah, seorang guru Tilawati, 22 siswa kelas V B, dan dua orang tua, serta dokumentasi program pembelajaran. Analisis data dilakukan melalui kondensasi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diuji melalui triangulasi sumber, triangulasi teknik, dan member check. Hasil penelitian menunjukkan bahwa metode Tilawati diterapkan melalui pembelajaran klasikal, baca-simak individual, koreksi langsung, evaluasi berkala, dan pembiasaan melalui program Khotmul Qur'an. Implementasi tersebut membantu siswa meningkatkan kelancaran, ketepatan tajwid, kestabilan irama bacaan, dan kepercayaan diri dalam tadarus. Guru berperan sebagai model bacaan, pembimbing, motivator, dan evaluator. Keberhasilan penerapan didukung oleh kompetensi guru, budaya religius madrasah, program yang terstruktur, dan dukungan keluarga, sedangkan hambatannya meliputi heterogenitas kemampuan siswa, keterbatasan waktu, dan pendampingan di rumah yang belum merata. Temuan menegaskan bahwa metode Tilawati efektif ketika diterapkan secara konsisten dan didukung sinergi sekolah dengan keluarga.